At My Mother's Knee ... and Other Low Joints - O'Grady, Paul, 1955- (London Bantam Press, 2008)
In his own uniquely acid tongue, Paul OGrady traces the hilarious tales of life in Irish Catholic Birkenhead that took him from a virtuous altar-boy (my first drag) to Britains best loved entertainer.
Include Illustration and Index
Keywords: Television personalities -- Great Britain -- O'Grady, Paul, 1955-